2022
DOI: 10.1002/elsa.202100182
|View full text |Cite
|
Sign up to set email alerts
|

Ambipolar diarylnitroxides: Molecular design and electrochemical testing

Abstract: Possible approaches to molecular design of stable diarylnitroxyl radicals capable to form sufficiently stable cations and anions under one‐electron oxidation and reduction are discussed. Both covalent and noncovalent stabilizing “tools” are considered. The main focus is made on the dynamic stabilization of oppositely charged redox states of a molecule through conformational changes. The efficiency of the approaches was confirmed on a wide range of novel diarylnitroxides designed accordingly to the suggested gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 35 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…For example, Saal et al (112) demonstrated the ambipolar behavior of polymers containing 1,2,4-benzotriazinyl radical (Blatter radical). Future work should focus on ambipolar groups with greater stability and larger voltage differences for the n-type and p-type reactions (155,156).…”
Section: Figure 11mentioning
confidence: 99%
“…For example, Saal et al (112) demonstrated the ambipolar behavior of polymers containing 1,2,4-benzotriazinyl radical (Blatter radical). Future work should focus on ambipolar groups with greater stability and larger voltage differences for the n-type and p-type reactions (155,156).…”
Section: Figure 11mentioning
confidence: 99%